The Influence of Classical Guidance in Improving the Career Development of Class XI.F2 Students at SMAN 1 Rambatan - Maulida; Rafsel Tas’adi; Hadiarni; Irman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This research is motivated by the phenomenon of students who lack an understanding of their self-potential (interests, talents, and abilities) in determining future career goals. This study aims to examine the significant influence of classical guidance in improving the career development of class XI F2 students at SMAN 1 Rambatan. The research method employed is quantitative research with an experimental type and a one-group pre-test post-test design. The population of this study consists of 29 students from class XI F2 at SMAN 1 Rambatan. The sampling technique used was total sampling, involving all 29 students. The research instrument used was a career development scale, which was validated with 48 question items. The results showed that there is a significant influence of classical guidance in improving students' career development. This is evident from the overall hypothesis testing where the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It was found that the trait and factor technique in classical guidance successfully improved students' career development at SMAN 1 Rambatan. Furthermore, career development scores showed an increase; the pre-test total score was 2,594 (average 89.44), which increased after treatment (post-test) to a total score of 2,938 (average 101.31).